Comparison of two different methods of prosthesis placement in otosclerosis - Bulgurcu, Suphi; Burak Arslan, Ilker; Ugur, Ömer; Cukurova, İbrahim (ENT Updates, 2019)
Objective: Objective: Choice and positioning of the pros thesis is a fundamental element in successful operations for otosclerosis. The present study compares two different techniques for placing a prosthesis when undertaking surgery for otosclerosis. Materials and Methods: A retrospective review was undertaken of records from 50 cases of individuals (33 women, 17 men) undergoing stapedotomy between the years 2009 and 2016. Two alternative procedures were used: in the “reverse” technique, placement of the prosthesis preceded stapes removal; in the “conventional” technique, placement of the prosthesis followed stapes removal. These groups were labelled groups 1 and 2, respectively. There were 25 cases in each. The two groups were compared for hearing outcome and incidence of complications. Results: An air-bone gap below 20 dB was obtained in 80% of cases following the reverse technique, and 76% of cases after conventional surgery. The difference between the two techniques lacked statistical significance (p>0.05). A single case in group 1 required a revision procedure since the prosthesis was taken out 4 months post-surgery. In group 2, a single case sustained injury to the chorda tympani. Vertigo symptoms occurred in 7 individuals in group 1, and 8 in group 2. Conclusion: There is no significant difference between treatments in terms of improved auditory function or fewer complications. The authors suggest clinicians’ experience is the key factor in deciding which technique to favour.